Unveiling Wolbachia transcriptomic signature in the arboviral vector Aedes aegypti - Mejías, Sebastián; Jiménez, Natalia E.; Conca, Carlos; Salgado, J. Cristian; Gerdtzen, Ziomara P. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe mosquito Aedes aegypti is the main vector of arboviral diseases such as dengue and imposes a global health burden. A promising control strategy is to infect A. aegypti populations with Wolbachia, a genus of intracellular bacteria capable of blocking arboviral infections. Enhancing and preserving the efficacy of this method will depend on a solid mechanistic knowledge of the A. aegypti-Wolbachia symbiosis. By identifying differences between Wolbachia-infected and uninfected A. aegypti, previous transcriptomic studies proposed a wide range of symbiotic interactions, but a systematic identification of consistent effects across datasets is still missing.MethodsTo identify A. aegypti genes and functions consistently affected by Wolbachia, we performed differential expression and functional enrichment analysis on published transcriptomic datasets, followed by a meta-analysis of the obtained p-values using the maxP method. Six datasets were retrieved from Gene Expression Omnibus, Sequence Read Archive and ArrayExpress (last searched in July 2024, considering lack of replication as the exclusion criteria). After discarding one dataset from wAlbB-infected cell line due to poor mapping to the A. aegypti genome, the data comprised adult female A. aegypti heads, muscles, carcasses, midguts and bodies, and Wolbachia strains wMel and wMelPop.Results and DiscussionMeta-analysis revealed 10 and 21 consistently down- and upregulated host genes, some of which have escaped the focus of previous research, including the consistently downregulated exonuclease AAEL009650 which has a pro-dengue virus homolog in Drosophila. At the function level, we found consistent upregulation of electron transport chain (ETC), carbohydrate transport and serine-type peptidase activity and inhibition, and downregulation of DNA replication. ETC upregulation suggests an alternative mechanism for Wolbachia’s induction of antiviral oxidative stress, previously attributed to dual- and NADPH-oxidases which here showed downregulation or no regulation. Through analysis of previously published datasets, this work identifies promising molecular and functional targets for future studies aimed at elucidating the most fundamental mechanisms of the A. aegypti–Wolbachia symbiosis.